Tubercular Pericardial Effusion Presenting as Cardiac Tamponade: A case report - Pradhan, Alok; Jasaraj, Ranjit Babu; Karki, Bhesh Raj; Joshi, Anish (Journal of Nepal Health Research Council, 2021)
Pericardial effusion is an uncommon extra-pulmonary manifestation of tuberculosis, tamponade being even rarer. Here, a 14-year female presented with cough, chest pain and fever. She had raised jugular venous pressure, hypotension, and muffled heart sound, suggestive of cardiac tamponade, confirmed by echocardiogram. She underwent pericardiocentesis with continuous pericardial fluid drainage. Her jugular venous pressure normalized after the aspiration. The high adenosine deaminase level in pericardial fluid analysis was suggestive of tuberculosis for which she was treated with antitubercular therapy and steroid. This case highlights the importance of adenosine deaminase for diagnosing the etiology of a rare presentation.Keywords: Adenosine deaminase; echocardiography; pericardial effusion; tamponade; tuberculosis